Targeted therapy using engineered extracellular vesicles: principles and strategies for membrane modification - Qisong Liu; Defeng Li; Xiaohua Pan; Yujie Liang (Journal of Nanobiotechnology, 2023)
Abstract Extracellular vesicles (EVs) are 30–150 nm membrane-bound vesicles naturally secreted by cells and play important roles in intercellular communication by delivering regulatory molecules such as proteins, lipids, nucleic acids and metabolites to recipient cells. As natural nano-carriers, EVs possess desirable properties such as high biocompatibility, biological barrier permeability, low toxicity, and low immunogenicity, making them potential therapeutic delivery vehicles. EVs derived from specific cells have inherent targeting capacity towards specific cell types, which is yet not satisfactory enough for targeted therapy development and needs to be improved. Surface modifications endow EVs with targeting abilities, significantly improving their therapeutic efficiency. Herein, we first briefly introduce the biogenesis, composition, uptake and function of EVs, and review the cargo loading approaches for EVs. Then, we summarize the recent advances in surface engineering strategies of EVs, focusing on the applications of engineered EVs for targeted therapy. Altogether, EVs hold great promise for targeted delivery of various cargos, and targeted modifications show promising effects on multiple diseases. Graphical Abstract